Kawashima by Fenestrated Hemi-Fontan for Palliation Following Prior Stage I Norwood Operation. Issue 4 (July 2018) - Zablah, Jenny E.; Ross, Michael; Wilson, Neil; Fonseca, Brian; Mitchell, Max B.
Single ventricle patients with interrupted inferior vena cava (IVC) and azygos continuation to the superior vena cava (SVC) are typically palliated with a bidirectional cavopulmonary shunt (BCPS), known as the Kawashima operation in this setting. Because the volume of venous blood directed to the pulmonary arteries is substantially greater in the presence of interrupted IVC, Kawashima procedures are commonly delayed to older age compared to other single ventricle patients undergoing BCPS. We report two young infant single ventricle patients with interrupted IVC and azygos continuation to the SVC who underwent stage I Norwood procedures for initial palliation. In both cases, a fenestrated hemi-Fontan procedure achieved successful Kawashima circulations.